COVID‐19 Pandemic: Management and Challenges - Parisa Saberi-Hasanabadi; Hamidreza Mohammadi (Mazandaran University of Medical Sciences, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an ongoing pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‑CoV‑2). The outbreak was first identified in Wuhan, China, in December 2019. Objectives: This review gives a bird's-eye view of the COVID-19 pandemic and its various effects on human society. Since knowledge about this virus is rapidly evolving, readers are urged to update themselves regularly. Methods: In this review, our searching was performed on international databases of Embase, ScienceDirect, Scopus, PubMed, and Web of Science (ISI) from October 2019 to June 2020. Results: Most patients infected with COVID‑19 have mild symptoms. Approximately 15% of patients have severe pneumonia, and about 5% acute distress syndrome or organ failure. In the absence of definitive treatment and vaccines, the most effective measure is to prevent infection, particularly in those at high risk of taking the severe form of the disease with adverse outcomes. Pharmacotherapy is essentially supportive; the role of antiviral agents is yet to be established. The commonest drugs used in treating this viral disease are tocilizumab, remdesivir, favipiravir, and camostat mesilate. Also, drugs related to malaria, AIDS, and Ebola, such as hydroxychloroquine, are widely used. Based on physical examinations alone, it is impossible to comment with certainty in mild cases of the disease. Accordingly, a wide range of methods is used for diagnosing and treating the disease. Various variables in reducing the severity of the epidemic and the effects of the virus require special management at the national, regional, and global levels. Conclusion: This review summarizes the latest findings in safety, management, and public services related to the COVID-19 virus epidemic.